IAS/IFRS and financial reporting quality: Lessons from the European experience - Vera Palea (China Journal of Accounting Research, 2013)
This paper discusses the effects of the adoption of IAS/IFRS in Europe on the quality of financial reporting. In doing so, it adopts the perspective of stock market investors and focuses on value-relevance research. The adoption of IAS/IFRS in Europe is an example of accounting standardization among countries with different institutional frameworks and enforcement rules. This allows investigating whether, and to what extent, accounting regulation per se can affect the quality of financial reporting and leads to convergence in financial reporting. This is a key issue for standard setting purposes as IAS/IFRS have been adopted in very diverse countries all over the world, and many others are likely to adopt them in the near future.
Keywords: M41; G10; 650; Financial reporting quality; IAS/IFRS; Value-relevance; European Regulation 1606/2002